MOTION DESIGN AS A TOOL OF EMOTIONAL IMPACT IN THE DIGITAL ENVIRONMENT - Assembek Saniya, (International Journal of Innovative Technologies in Social Science, 2025)
Objective: The integration of animated elements into digital environments has transformed motion design into a core tool for emotional communication. This study investigates how specific motion parameters influence emotional perception and user engagement across platforms.Methods: A mixed-method design was employed, combining content analysis of 20 motion-based digital products, semi-structured interviews with six professional motion designers, and an evaluative user study involving 20 participants. Visual rhythm, transition timing, pacing, and animation types were analyzed alongside self-reported emotional responses and expert commentary.Key findings: Smooth transitions and fade-in effects were strongly associated with calmness and trust, while sharp cuts and pulsing animations evoked urgency and tension. Designers emphasized rhythm and timing as key emotional drivers, though cited challenges in standardizing affective outcomes across platforms. User testing showed 70% alignment between intended and perceived emotions. Engagement was highest for synchronized animations on social media platforms, with content reveal sequences receiving the strongest positive response.Conclusions: Motion design functions as an affective layer of digital interaction, capable of modulating user emotion when calibrated effectively. Combining designer intent with real-time user feedback and platform specificity is critical for emotionally intelligent digital communication. Further development of standardized affective frameworks may enhance consistency and design precision.